2022
DOI: 10.3390/biology11030348
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding Transcriptome Provides Novel Insights into the Escherichia coli F17 Susceptibility of Sheep Lamb

Abstract: It has long been recognized that enterotoxigenic Escherichia coli (ETEC) is the major pathogen responsible for vomiting and diarrhea. E. coli F17, a main subtype of ETEC, is characterized by high morbidity and mortality in young livestock. However, the transcriptomic basis underlying E. coli F17 infection has not been fully understood. In this study, RNA sequencing was performed to explore the expression profiles of circRNAs and miRNAs in the jejunum of E. coli F17-antagonism (AN) and -sensitive (SE) lambs. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 75 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…The rapid spread of sheep diseases has led to an increase in the culling of sheep and losses to breeding farms. Escherichia coli infections are a major threat to young animals and can be fatal in severe cases [ 51 , 52 ]. Therefore, the breeding of high quality disease-resistant sheep is an important issue, and the use of key genes or candidate sites that influence the occurrence of sheep diseases can improve the economic benefits of breeding enterprises and promote the healthy development of the sheep industry.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid spread of sheep diseases has led to an increase in the culling of sheep and losses to breeding farms. Escherichia coli infections are a major threat to young animals and can be fatal in severe cases [ 51 , 52 ]. Therefore, the breeding of high quality disease-resistant sheep is an important issue, and the use of key genes or candidate sites that influence the occurrence of sheep diseases can improve the economic benefits of breeding enterprises and promote the healthy development of the sheep industry.…”
Section: Discussionmentioning
confidence: 99%
“…A. Jaeger et al found that many miRNAs were significantly up-regulated in porcine mammary epithelial cells attacked for 3 and 24 h [44]. Chen et al conducted RNA sequencing on the ileal tissues of sheep that were either E. coli F17-sensitive or antagonistic, identifying differentially expressed miRNAs and circRNAs, and constructing the corresponding ceRNA networks [45]. Therefore, in this study, we selected the screened differentially expressed miR-329b-5p to investigate the role of miRNAs against E. coli infection in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we compared the classification accuracy of several decision tree-based machine learning approaches (Random Forest, XGBoost, and RX) and DE transcript identification methods (edgeR and t -test) in subsets of transcriptomic data. The results showed that a method combining Random Forest and XGBoost (RX) outperformed the other four methods (Random Forest, XGBoost, t -test, and edgeR) with the highest classification accuracy and showed biological value in the prediction of multiple traits such as feed efficiency ( 26 ) and Escherichia coli infection ( 60 ).…”
Section: Discussionmentioning
confidence: 99%